The role of neighborhood characteristics for firm performance in the experience economy: A case study of production volumes in California's Brewpub industry - Rebekka E. Apardian; Isabelle Nilsson; Neil Reid; Julie Wartell (Journal of Urban Management, 2022)
The number of craft breweries in the United States grew from 37 in 1985 to over 8,000 in 2019, establishing craft breweries as a ubiquitous feature of the American landscape. At a time when consumers are increasingly shifting their spending from material goods to experiences, the craft brewery industry is a quintessential example of this burgeoning experience economy. Local craft breweries sell a sensorial experience along with their product. By engaging in adaptive reuse of abandoned buildings, combining production and sales under the same roof, offering educational tours, and providing other activities (e.g., board games) for patrons to enjoy, many craft breweries offer a unique venue to enjoy a pint of locally made beer. While the internal appeal of craft breweries and beer contributes to their popularity, our focus in this paper is the role of external neighborhood characteristics in understanding performance variations among a specific type of craft brewery - brewpubs. Many brewpubs are located in mixed-use gentrified neighborhoods, where they co-exist with coffee shops, restaurants, retail boutiques, and other drinking establishments. We use California as our case study and production volumes as a proxy for performance to explore the effect of neighborhood characteristics on brewpub performance. We find that neighborhood variables associated with variations in brewpub production volumes varies depending on whether the brewpub is located in a city or rural area. However, brewpub production volumes in both urban and non-urban areas are negatively associated with neighborhood property values and positively associated with nearby clustering of other drinking establishments. This suggests a desire for affordable production space and illustrates a positive impact of clustering with similar establishments in a neighborhood. Hence, allowing these establishments to locate in areas zoned for commercial activities may be important for their success. Interestingly, walkability was found to have no significant effect on brewpub performance in urban areas while it was found to have significant effect in non-urban areas, suggesting that non-urban areas may be able to increase production by encouraging more walkable environments.
Keywords: 710; Experience economy; Brewpubs; Production volumes; Neighborhood characteristics; California